Linking the Congenital Heart Surgery Databases of the Society of Thoracic Surgeons and the Congenital Heart Surgeons' Society: Part 2—Lessons Learned and Implications. (April 2014) - Jacobs, Jeffrey P.; Pasquali, Sara K.; Austin, Erle; Gaynor, J. William; Backer, Carl; Hirsch-Romano, Jennifer C.; Williams, William G.; Caldarone, Christopher A.; McCrindle, Brian W.; Graham, Karen E.; Dokholyan, Rachel S.; Shook, Gregory J.; et al.
Purpose: A link has been created between the Society of Thoracic Surgeons Congenital Heart Surgery Database (STS-CHSD) and the Congenital Heart Surgeons' Society Database (CHSS-D). Five matrices have been created that facilitate the automated identification of patients who are potentially eligible for the five active CHSS studies using the STS-CHSD. These matrices are now used to (1) estimate the denominator of patients eligible for CHSS studies and (2) compare "eligible and enrolled patients" to "potentially eligible and not enrolled patients" to assess the generalizability of CHSS studies. Methods: The matrices were applied to 40 consenting institutions that participate in both the STS-CHSD and the CHSS to (1) estimate the denominator of patients that are potentially eligible for CHSS studies, (2) estimate the completeness of enrollment of patients eligible for CHSS studies among all CHSS sites, (3) estimate the completeness of enrollment of patients eligible for CHSS studies among those CHSS institutions participating in each CHSS cohort study, and (4) compare "eligible and enrolled patients" to "potentially eligible and not enrolled patients" to assess the generalizability of CHSS studies. The matrices were applied to all participants in the STS-CHSD to identify patients who underwent frequently performed operations and compare "eligible and enrolled patients" to "potentially eligible and not enrolled patients" in following five domains: (1) age at surgery, (2) gender, (3) race, (4) discharge mortality, and (5) postoperative length of stay. Completeness of enrollment was defined as the number of actually enrolled patients divided by the number of patients identified as being potentially eligible for enrollment. Results: For the CHSS Critical Left Ventricular Outflow Tract Study (LVOTO) study, for the Norwood procedure, completeness of enrollment at centers actively participating in the LVOTO study was 34%. For the Norwood operation, discharge mortality was 15% among 227 enrolled patients and 16% among 1768 nonenrolled potentially eligible patients from the 40 consenting institutions. Median postoperative length of stay was 31 days and 26 days for these enrolled and nonenrolled patients. For the CHSS anomalous aortic origin of a coronary artery (AAOCA) study, for AAOCA repair, completeness of enrollment at centers actively participating in the AAOCA study was 40%. Conclusion: Determination of the denominator of patients eligible for CHSS studies and comparison of "eligible and enrolled patients" to "potentially eligible and not enrolled patients" provides an estimate of the extent to which patients in CHSS studies are representative of the overall population of eligible patients; however, opportunities exist to improve enrollment.